2013
DOI: 10.1186/2193-1801-2-243
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative radiological margins assessment in conservative treatment for non-palpable DCIS: correlation to pathological examination and re-excision rate

Abstract: What constitutes an adequate surgical margin in partial mastectomy is still controversial: intra-operative specimen radiogram is commonly used during partial mastectomy for nonpalpable lesions in order verify the adequacy of the resection but what margin is to be considered “adequate” is still debatable.An intraoperative specimen mammogram was performed during all consecutive conservative resections for nonpalpable DCIS and a 15-mm radiological margin was considered “adequate”. Margins were pathologically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…The Kappa coeffi cient in our study of 0.25 showed a fair level of agreement between surgeon and radiologist. Previous studies showed that tumour grade, type and size did not infl uence margin assessment[30][31]. In this study, such conclusions could not be drawn due to the size of the patient cohort and the low positive margin rate.…”
contrasting
confidence: 67%
“…The Kappa coeffi cient in our study of 0.25 showed a fair level of agreement between surgeon and radiologist. Previous studies showed that tumour grade, type and size did not infl uence margin assessment[30][31]. In this study, such conclusions could not be drawn due to the size of the patient cohort and the low positive margin rate.…”
contrasting
confidence: 67%
“…In this study, one of the objectives was to determine the optimal cutoff value of radiological margin to be used for predicting resection margin adequacy for DCIS, and ROC curves showed that a 15-mm radiological margin had the highest combination of sensitivity and specificity. Using a radiological margin of 15 mm was supported by Buggi et al, 26 Table 6. Studies reviewing accuracy of specimen radiography in predicting resection margin status in early breast cancers.…”
Section: Discussionmentioning
confidence: 94%
“…17,22 The reported sensitivity and specificity of specimen radiography in predicting resection margin status for early breast cancer ranges from 33% to 75% and 65% to 95%, respectively. 17,[19][20][21][22][23][24][25][26] Such heterogeneous data may be partially explained by the lack of international consensus regarding the optimal pathological and radiological margin to be used. Pathological margins of no ink on tumour, 1 mm, 2 mm, and 5 mm have all been used in previous studies, while the radiological margins used varied from 0 mm (lesion reaching specimen border) to 15 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations